DNA Methylation Epigenetically Regulates Gene Expression in Burkholderia cenocepacia and Controls Biofilm Formation, Cell Aggregation, and Motility - Ian Vandenbussche (American Society for Microbiology, 2020)
ABSTRACT Respiratory tract infections by the opportunistic pathogen Burkholderia cenocepacia often lead to severe lung damage in cystic fibrosis (CF) patients. New insights in how to tackle these infections might emerge from the field of epigenetics, as DNA methylation is an important regulator of gene expression. The present study focused on two DNA methyltransferases (MTases) in B. cenocepacia strains J2315 and K56-2 and their role in regulating gene expression. In silico predicted DNA MTase genes BCAL3494 and BCAM0992 were deleted in both strains, and the phenotypes of the resulting deletion mutants were studied: deletion mutant ΔBCAL3494 showed changes in biofilm structure and cell aggregation, while ΔBCAM0992 was less motile. B. cenocepacia wild-type cultures treated with sinefungin, a known DNA MTase inhibitor, exhibited the same phenotype as DNA MTase deletion mutants. Single-molecule real-time sequencing was used to characterize the methylome of B. cenocepacia, including methylation at the origin of replication, and motifs CACAG and GTWWAC were identified as targets of BCAL3494 and BCAM0992, respectively. All genes with methylated motifs in their putative promoter region were identified, and qPCR experiments showed an upregulation of several genes, including biofilm- and motility-related genes, in MTase deletion mutants with unmethylated motifs, explaining the observed phenotypes in these mutants. In summary, our data confirm that DNA methylation plays an important role in regulating the expression of B. cenocepacia genes involved in biofilm formation, cell aggregation, and motility. IMPORTANCE CF patients diagnosed with Burkholderia cenocepacia infections often experience rapid deterioration of lung function, known as cepacia syndrome. B. cenocepacia has a large multireplicon genome, and much remains to be learned about regulation of gene expression in this organism. From studies in other (model) organisms, it is known that epigenetic changes through DNA methylation play an important role in this regulation. The identification of B. cenocepacia genes of which the expression is regulated by DNA methylation and identification of the regulatory systems involved in this methylation are likely to advance the biological understanding of B. cenocepacia cell adaptation via epigenetic regulation. In time, this might lead to novel approaches to tackle B. cenocepacia infections in CF patients.